Homeopathy Therapeutically Uses Homeopathic Medicines, but Also Narratives, which are Integrated into Compassionate Care: A Comparison between Homeopathic Medicine and Narrative Medicine - Tarro, Giulio; De Giorgio, Giovanni (British Journal of Healthcare and Medical Research, 2025)
Homeopathy, founded about two centuries ago by Samuel Hahnemann, is a clinical methodology based on the law of similarity and, both in diagnosis and therapy, takes this fundamental law into account. During homeopathic treatments, small doses of substances are administered which, if administered in high doses, would produce symptoms similar to those that need to be treated. In a homeopathic treatment, homeopathic medicines are used therapeutically, but also narratives, which are integrated into a compassionate treatment, typically Hahnemannian, supported by a clinically holistic, global, human approach, guided by compassion and the awareness that similar is cured by similar: similia similibus curentur. Homeopathy, which today also makes use of important knowledge acquired with rigorous scientific research, homeopathically uses narratives in an integrative therapeutic function, therefore, we consider a comparison between homeopathic medicine and narrative medicine useful, interesting and scientifically constructive.